“Pengembangan Media Pembelajaran Website Berbasis Google Sites Untuk Meningkatkan Kebhinekaan Global Anak Usia Dini Di TK IT Almawaddah Tahun Pelajaran 2022/2023“ - Murgiyanti Murgiyanti (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
The purpose of this development research is to determine media development, validity, practicality, effectiveness. This research method uses the Research and Development (R&D) method in the ADDIE development model which has five stages, namely analysis, design, development, implementation, and evaluation. A limited-scale trial was conducted on 18 class A2 students at TK IT Almawaddah and a large-scale trial was conducted on 36 class A students at TK IT Almawaddah. The data obtained is in the form of documentation and scores. The data analysis techniques used were interviews, need assessments, validation questionnaires, practicality questionnaires, and posttests. The validity results obtained are very valid criteria with a score of 95% for material experts and 86% for media experts. The results of the media practicality test obtained very practical criteria with a score of 93.75%. From these results it can be concluded that media websites based on Google sites are appropriate to be used to increase the global diversity of early childhood. It is expected that media websites based on google sites can be developed again by teachers or advanced researchers.